2015
DOI: 10.1002/rra.2878
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Influencing Macrophytes Assemblages in a Middle-Sized Mediterranean Stream

Abstract: The occurrence of aquatic plants was analysed in a medium-sized river in Greece. There were three objectives. The first was to examine the macrophyte assemblage structure along the river. The identification and hierarchical structure of aquatic plant assemblages were analyzed using Bray-Curtis analysis. Taxa primarily responsible for the differences among the assemblages were identified using similarity percentage analysis. The second objective was to investigate whether habitat features have greater impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…However, these characteristics are quite frequently mentioned as being responsible for species composition of similar water bodies (Lacoul & Freedman 2006). On the other hand, the strong effect of landscape and hydromorphological variables on species composition in contrast to physico-chemical variables is well documented from aquatic habitats in Slovakia and other European countries Dorotovičová 2013;Hrivnák et al 2013;Baláži & Hrivnák 2015;Manolaki & Papastergiadou 2015). Among these hydromorphological variables, mainly land-use type, sediment structure, water depth and width respectively were detected as the most significant.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, these characteristics are quite frequently mentioned as being responsible for species composition of similar water bodies (Lacoul & Freedman 2006). On the other hand, the strong effect of landscape and hydromorphological variables on species composition in contrast to physico-chemical variables is well documented from aquatic habitats in Slovakia and other European countries Dorotovičová 2013;Hrivnák et al 2013;Baláži & Hrivnák 2015;Manolaki & Papastergiadou 2015). Among these hydromorphological variables, mainly land-use type, sediment structure, water depth and width respectively were detected as the most significant.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have shown that ammonium concentrations and phosphates in water affect the composition in aquatic plant communities and ammonium ion is the preferred nitrogen source for plant growth (Bornette & Puijalon 2011). Electrical conductivity (Ferreira et al 1998;Sabbatini et al 1998;Dorotovičová 2013;Manolaki & Papastergiadou 2015) and water pH (Ferreira et al 1998) are often discussed as other chemical variables influencing the occurrence of aquatic plants. An intensive application of pesticides, sewage and industrial effluents from towns and cities are the main sources of organic pollution.…”
Section: Discussionmentioning
confidence: 99%
“…That geomorphological variables greatly affect plant spatial distribution has been previously demonstrated in Mediterranean streams [ 29 ] and in wetlands [ 26 ], but has not been previously assessed in ditches. This is reasonable for ditches because geomorphological features control the water regime and consequently greatly influence the fluxes of sediments, nutrients, pesticides and plant propagules that reach the ditches.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the global sun exposure of the hillslopes and the solar radiation are known to affect the temperature conditions in streams and the plant responses to light [ 28 ]. Geomorphological variables were found to be good predictors of aquatic plant assemblages by Manolaki and Papastergiadou [ 29 ], who focused on the distribution of macrophytes in Mediterranean rivers. Maheu-Giroux and de Blois [ 30 ] emphasized that although the geomorphology of ditches may be a major factor explaining the spatial distribution of species, geomorphology is seldom considered in studies concerning linear hydro-agroecological infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Así mismo, se observaron variaciones en relación con las variables fisicoquímicas, aunque estas fueron más representativas entre sistemas que entre muestreos, caso particular el del río Guarinó, donde se presentaron los valores más altos de variables relacionadas con el transporte de sedimentos, como turbiedad, conductividad eléctrica, color aparente, sólidos suspendidos totales, entre otras. Lo que es favorecido por el predominio del sustrato arenoso en el cauce del río, sustrato que no es predominante en ríos de alta montaña, pero por los diversos usos del suelo aguas arriba y en inmediaciones de la estación, se ven alteradas las condiciones naturales de dicho sistema Las variables fisicoquímicas medidas, presentan una relación importante con la conformación de la estructura biológica de interés, en otras investigaciones se ha evidenciado que variables como conductividad y temperatura, tipo de sustrato, nutrientes como nitrógeno y fósforo en sus formas iónicas disponibles, caudal y velocidad de la corriente, explican en gran medida la distribución y presencia de la vegetación acuática [14], [35], [37], dichas variables en el ecosistema natural influyen en el crecimiento de las plantas como el caso de los nutrientes, por otra parte variables como el caudal y temperatura condicionan la presencia o ausencia de algunos taxa.…”
Section: Análisis De Resultados Y Discusiónunclassified